A novel imidazopyridine derivative, X22, prevents the retinal ischemia-reperfusion injury via inhibition of MAPKs. (June 2015) - Bian, Yang; Ren, Luqing; Wang, Lei; Xu, Shanmei; Tao, Jianjian; Zhang, Xiuhua; Huang, Yi; Qian, Yuanyuan; Zhang, Xin; Song, Zongming; Wu, Wencan; Wang, Yi; et al.
Abstract: Inflammation is a pathological hallmark of ischemia reperfusion (I/R) injury. The present study was conducted to explore the ability of a new anti-inflammatory compound, X22, to attenuate retinal I/R injury via cytokine-inhibitory mechanism. For the in vitro experiment, ARPE-19 cells were pretreated with X22 (5 or 10 μM) or saline for 2 h, followed by stimulation with tert-butyl hydroperoxide (TBHP, 1000 μM) for an indicated amount of time. The expression of inflammatory mediators, cell viability, and cell apoptosis were evaluated. For the in vivo experiment, the rats were randomized to receive treatment with saline or X22 (0.1 μM/kg, 3 μL) before the induction of I/R injury. Histological evaluation, apoptosis of retinal cells, macrophage infiltration, and retina functional changes were further determined. Our data showed that pretreatment with X22 significantly inhibited TBHP-induced inflammatory cytokine expression in ARPE-19 cells. The anti-inflammatory activity of X22 may be associated with its inhibition on MAPKs, rather than NF-κB. Subsequently, our data proved that TBHP induced apoptosis in ARPE-19 cells, while pretreatment of X22 significantly suppressed TBHP-caused ARPE-19 apoptosis. Finally, the in vivo data revealed that X22 administration maintained better inner retinal layer structures, reduced apoptosis of retinal ganglion cell, and improved retinal function in retinal I/R rat models, which were accompanied with a remarkable decrease in retinal macrophage infiltration. These results suggest that the novel compound X22 is a potential agent for the treatment of retinal I/R-related diseases via the MAPKs-targeting anti-inflammatory mechanism and deserves the further development. Highlights: Inflammation is a pathological hallmark of ischemia reperfusion (I/R) injury. X22 is a novel imidazopyridine derivative with anti-inflammatory effects. Pretreatment with X22 inhibited TBHP-induced inflammation and apoptosis in vitro . The anti-inflammatory activity of X22 is associated with its inhibition on MAPKs. X22 administration reduced retinal I/R injury in vivo .